2008
DOI: 10.1016/j.vaccine.2008.02.009
|View full text |Cite
|
Sign up to set email alerts
|

The relative contribution of antibody and CD8+ T cells to vaccine immunity against West Nile encephalitis virus

Abstract: West Nile virus (WNV) is a mosquito borne, neurotropic flavivirus that causes a severe central nervous system (CNS) infection in humans and animals. Although commercial vaccines are available for horses, none is currently approved for human use. In this study, we evaluated the efficacy and mechanism of immune protection of two candidate WNV vaccines in mice. A formalin-inactivated WNV vaccine induced higher levels of specific and neutralizing antibodies compared to a DNA plasmid vaccine that produces virus-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 59 publications
2
47
1
Order By: Relevance
“…However, such an immunopathology role of CD8 ϩ T cells was likely not due to their cytotoxic functions, because these cells are usually activated after 1 week postinfection. In support of this, the same study and many other reports also showed a recovery role of CD8 ϩ T cells when mice were infected with low doses (10 2 to 10 3 PFU) of WNV, which is similar to the current study (12,92,(95)(96)(97)(98). In addition, Th17 cells and IL-17A have been implicated in inflammation and immunopathology associated with autoimmune diseases (25)(26)(27) and some virus-induced chronic CNS diseases (48,99,100), suggesting that Th17/IL-17A axis may have different implications under such immunopathological and chronic inflammatory conditions.…”
Section: Discussionsupporting
confidence: 92%
“…However, such an immunopathology role of CD8 ϩ T cells was likely not due to their cytotoxic functions, because these cells are usually activated after 1 week postinfection. In support of this, the same study and many other reports also showed a recovery role of CD8 ϩ T cells when mice were infected with low doses (10 2 to 10 3 PFU) of WNV, which is similar to the current study (12,92,(95)(96)(97)(98). In addition, Th17 cells and IL-17A have been implicated in inflammation and immunopathology associated with autoimmune diseases (25)(26)(27) and some virus-induced chronic CNS diseases (48,99,100), suggesting that Th17/IL-17A axis may have different implications under such immunopathological and chronic inflammatory conditions.…”
Section: Discussionsupporting
confidence: 92%
“…The protection obtained in the ␤2m Ϫ/Ϫ mouse model confirms that the heterologous protection conferred by JE-ADVAX does not depend on memory CD8 ϩ T cells, high levels of IFN-␥ production, or prechallenge serum neutralizing antibody. However, the result does not exclude the possibility not investigated here that memory CD8 ϩ T cells play a supportive role in JE-ADVAX-mediated protection, given previous demonstrations that CD8 T cells can contribute to single-dose, although not two-dose, WNV vaccine protection (58), adoptive transfer of WNV-specific T cells was able to protect against WNV infection (66), and induction of WNV-specific T cells by DNA immunization with single-chain HLA-A2 major histocompatibility complex trimer molecules incorporating an immune-dominant WNV peptide derived from the E protein was also able to provide protection (67).…”
Section: Cd8contrasting
confidence: 78%
“…The titer was defined as the serum dilution yielding an optical density at 450 nm equivalent to three times above the background of the assay. The titer of neutralizing antibody was determined by using a plaque reduction neutralization assay with BHK21-15 cells (36). Plaques were counted visually and plotted, and the plaque reduction neutralization titer for 50% inhibition (PRNT 50 ) was calculated using GraphPad Prism software.…”
Section: Methodsmentioning
confidence: 99%
“…Leukocytes were isolated from the brains of infected animals and quantified as described previously (36). Briefly, 8 days after subcutaneous infection with 10 2 PFU of WNV, brains were harvested after extensive perfusion with PBS, dispersed into single-cell suspensions, and digested with 0.05% collagenase D, 0.1 g/ml trypsin inhibitor TLCK (N␣-p-tosyl-L-lysine chloromethyl ketone), 10 g/ml DNase I (all from Sigma Chemical), and 10 mM HEPES, pH 7.3, in Hanks' balanced salt solution for 1 h. Leukocytes were isolated by discontinuous Percoll gradient (70%-37%-30%) centrifugation for 30 min (850 ϫ g at 4°C).…”
Section: Methodsmentioning
confidence: 99%